Interventions associated with brown adipose tissue activation and the impact on energy expenditure and weight loss: A systematic review - Perez, Luis C.; Perez, Laura T.; Nene, Yash; Umpierrez, Guillermo E.; Davis, Georgia M.; Pasquel, Francisco J. (Frontiers in Endocrinology, 2022)
BACKGROUND: Brown adipose tissue (BAT) plays a role in modulating energy expenditure. People with obesity have been shown to have reduced activation of BAT. Agents associated with activation of BAT in humans may promote weight loss. METHODS: We systematically searched electronic databases for clinical trials testing the effect β-agonists, capsinoids, thyroid hormone, sildenafil, caffeine and cold exposure on energy expenditure/thermogenesis and the extent to which they may impact weight loss in adults. RESULTS: A total of 695 studies from PubMed, Web of Science, and Medline electronic databases were identified. After the removal of duplicates and further evaluation, 47 clinical trials were analyzed. We observed significant heterogeneity in the duration of interventions and the metrics utilized to estimate thermogenesis/energy expenditure. Changes observed in energy expenditure do not correlate with major weight changes with different interventions commonly known to stimulate thermogenesis. Even though cold exposure appears to consistently activate BAT and induce thermogenesis, studies are small, and it appears to be an unlikely sustainable therapy to combat obesity. Most studies were small and potential risks associated with known side effects of some agents such as beta-agonists (tachycardia), sibutramine (hypertension, tachycardia), thyroid hormone (arrhythmias) cannot be fully evaluated from these small trials. CONCLUSION: Though the impact of BAT activation and associated increases in energy expenditure on clinically meaningful weight loss is a topic of great interest, further data is needed to determine long-term feasibility and efficacy.